Cardiovascular, perceptual, and performance responses to single- vs. multi-chambered blood flow restriction cuffs - Nicholas Rolnick; Nicholas Rolnick; Nicholas Rolnick; Victor S. de Queiros; Masoud Moghaddam; Evan Peikon; Susannah Taylor; Samantha Watson; Campbell Ruffhead; Sean Zupnik; Tim Werner (Frontiers Media S.A., 2024)
IntroductionThis study aimed to investigate the impact of the blood flow restriction bladder type (single- [SC-BFR] vs. multi-chambered [MC-BFR]) on exercise performance, cardiovascular responses, and perceptual experiences with exercise sessions incorporating multiple sets to volitional failure in a randomized, crossover experimental design.MethodsTwenty-seven healthy, physically active participants (age: 22.6 ± 5.7; weight: 74.3 ± 15.8 kg; height: 171.7 ± 7.7 cm; BMI: 25.0 ± 4.1 kg/m2; ∼93% reported regular resistance training within 6 months; 11 females) randomly performed exercise to failure (4× sets to failure, 20% 1RM, 1 min rest between sets) in each of three conditions: SC-BFR (using the Delfi Personalized Tourniquet Device inflated to 60% limb occlusion pressure), MC-BFR (using the B Strong Cuffs inflated to 300 mmHg according to manufacturer recommendations), and N-BFR (no BFR control).ResultsSC-BFR blunted post-exercise increases in carotid-femoral pulse wave velocity (p = 0.328) (+3.3%) whereas the other conditions showed elevations (MC-BFR +11.8% [p = 0.041], N-BFR +9.3% [p = 0.012]). Discomfort was lower in N-BFR compared to SC-BFR (p < 0.001) and MC-BFR (p = 0.035) but all displayed similar exertion (p = 0.176). Median total repetitions achieved were significantly less in SC-BFR (57 [25-75th percentile: 47-65) than MC-BFR (76 [63-91] (p = 0.043) and N-BFR [106 (97-148)] p = 0.005). Per set repetition volumes were similar on set 1 between SC-BFR (p < 0.001) and MC-BFR (p = 0.001) and were lower than N-BFR (p ≤ 0.001) whereas in sets 2-4, MC-BFR performed similar number of repetitions as N-BFR (p = 0.984-1.000).ConclusionBladder design of a BFR cuff has an impact on the acute responses to exercise if applied according to recommended application guidelines, as SC-BFR impacts performance to a greater degree and mitigates post-exercise arterial stiffness responses compared to MC-BFR and N-BFR while both BFR conditions display greater levels of discomfort compared to N-BFR. Clinical Trial RegistrationNCT06276673.